Etika Bisnis Kontemporer: Tinjauan dan Implikasinya terhadap Dunia Usaha - Indhytsania H, Rahma; Sikki, Nurhaeni; Tumbas, Gradiana; Mayusip, Billy; Mamengko, Waraney; Dotulong, Dean Joshua (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the dynamic realm of contemporary business ethics, emphasizing how globalization, technological advancements, and societal changes have transformed ethical standards in modern organizations. Employing a qualitative literature review method, this research synthesizes insights from academic journals, books, and reports published between 2015 and 2024. The findings reveal that contemporary business ethics are increasingly driven by corporate social responsibility (CSR), sustainability initiatives, diversity and inclusion (D&I) policies, and digital governance. Additionally, ethical leadership and stakeholder engagement have emerged as pivotal factors influencing ethical practices. The study concludes that businesses must continually adapt to evolving ethical expectations to maintain legitimacy and trust in an interconnected world.